2022
DOI: 10.3390/jpm12111846
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Medicine for Classical Anesthesia Drugs and Cancer Progression

Abstract: In this review, we aim to discuss the use and effect of five different drugs used in the induction of anesthesia in cancer patients. Propofol, fentanyl, rocuronium, sugammadex, and dexamethasone are commonly used to induce anesthesia and prevent pain during surgery. Currently, the mechanisms of these drugs to induce the state of anesthesia are not yet fully understood, despite their use being considered safe. An association between anesthetic agents and cancer progression has been determined; therefore, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Compared to other preanesthetic drugs, the use of scopolamine efectively reduces the dosage of anesthetic agents and, consequently, lowers the occurrence of postoperative adverse reactions. Multiple studies have suggested that perioperative anesthesia drugs can have an impact on the viability of tumor cells and signifcantly infuence patient prognosis [44,45]. In the prescreening drug experiment, this study discovered that scopolamine may possess the capability to inhibit the metastasis of tumor cells.…”
Section: Discussionmentioning
confidence: 92%
“…Compared to other preanesthetic drugs, the use of scopolamine efectively reduces the dosage of anesthetic agents and, consequently, lowers the occurrence of postoperative adverse reactions. Multiple studies have suggested that perioperative anesthesia drugs can have an impact on the viability of tumor cells and signifcantly infuence patient prognosis [44,45]. In the prescreening drug experiment, this study discovered that scopolamine may possess the capability to inhibit the metastasis of tumor cells.…”
Section: Discussionmentioning
confidence: 92%
“…Te rocuronium-induced neuromuscular blockade efect is similarly prolonged during liver resection in patients with hepatocellular carcinoma without preoperative hepatic impairment, but sugammadex reversal is efective [10]. Sugammadex, a potent antagonist of rocuronium bromide, is thought to promote recovery after surgery in cancer patients, but its efect on cancer cells has not been reported in studies, possibly because the drug's larger molecules do not enter cells [11].…”
Section: Resultsmentioning
confidence: 99%
“…A combination of rocuronium and propofol can provide excellent intubating conditions, reducing the discomfort of propofol administration. Combining opioids with rocuronium is also beneficial for intubation conditions and attenuates pain during administration ( Costa, Mourão & Vale, 2022 ). Moreover, the individual antitumor effects of propofol, sufentanil, and rocuronium make them potential candidates for combination therapy in the surgical management of lung cancer.…”
Section: Introductionmentioning
confidence: 99%